Evaluation of antimicrobial stewardship implementation in elective surgery in dr Cipto Mangunkusumo General Hospital using Gyssens Method - Ulima, Rhea P; Moenadjat, Yefta (UI Scholars Hub, 2024)
Introduction. Nowadays, surgical site infections (SSI) remain the most common complication of surgical procedures. In prevention, prophylactic antibiotics are the first option, which leads to the high use of antibiotics. However, antibiotic administration should be based on strategies such as stewardship. Thus, the study aimed to assess the situation using Gyssens' method. Method. A retrospective cohort study analyzed the antibiotic administration of most major elective surgeries, including thyroidectomy, mastectomy, and cholecystectomy, proceeded in Dr. Cipto Mangunkusumo General Hospital, Jakarta, Indonesia, from January to July 2023. Indication, type, dosage, timing, interval, duration, and route of administration were the variables of interest. Results. Of 191 subjects who underwent the most common elective surgery procedures, 30 used combination antibiotics. Gyssens category 0 consists of 165 subjects (86.5%), and 11 subjects (5.8%) were classified as category IIA, indicating inappropriate dose (inadequate, insufficient). Inaccuracies were identified as mistimed administration (5.8%), less effective antibiotic selection (3.1%), incorrect dosage (2.6%), and inappropriate timing (2.1%). The association of Gyssens categories with SSIs showed a p-value of > 0.05 with an odds ratio of 1, indicating that both appropriate and inappropriate antibiotics of the Gyssens category showed no impact on SSIs or non–SSIs. Conclusion. The adherence to antimicrobial stewardship in the most common elective surgery in the Department of Surgery, dr. Cipto Mangunkusumo General Hospital was 86.4 and subjected to improvement.